EFFECT OF RELATIVE HUMIDITY LEVELS ON LIFE PARAMETERS OF MICROTERMES UNICOLOR SNYDER (ISOPTERA: TERMITIDAE) FOR COLONY FORMATION UNDER LABORATORY CONDITIONS - Sattar, A.; Salihah, Z.; Naeem, R. (The Nucleus, 2020)
Effect of different relative humidity levels on the observable events i.e construction of copularium, oviposition period, eggs laid per female, eggs hatching, incubation period, development of workers, development of pre-soldier, and longevity of reproductive of Microtermes unicolor were studied in the laboratory at Nuclear Institute for Food and Agriculture (NIFA), Peshawar, Pakistan. Seventy seven pairs of the fungus growing termite M. unicolor were collected from the swarming and incipient colonies were established in the laboratory at 31, 45, 51, 63, 76 and 92% relative humidity levels in controlled temperature at 27 + 2 0C. Maximum (413) eggs laid per female, maximum hatching of eggs (14.28%), minimum incubation period (21 days), minimum 49 and 47 days for worker and soldier formation respectively, and maximum survival (130 days) were recorded on the 92% R.H. It was found that 92% R.H. was the best in all respects of termite activities. On other relative humidity levels, the primary reproductive survived only for a period of 2 to 3 weeks as well as the eggs laid by them remained unhatched.